Women With Cerebral Infarction Feature Worse Clinical Profiles at Admission but Comparable Success to Men During Long-Term Inpatient Neurorehabilitation - Alexandra Kautzky-Willer (Frontiers Media S.A., 2021)
Objective: Little is known about possible sex and gender differences in post-stroke neurorehabilitation outcomes. We aimed to analyze if functional performance, prevalence and impact of comorbidities at admission, and success of inpatient stroke-neurorehabilitation differ between men and women.Methods: Retrospective cohort analysis of 1,437 men and 907 women with prior cerebral infarction treated at a neurorehabilitation clinic between 2012 and 2017; multiple linear regression was used to examine the influence of sex/gender as well as multiple confounders on health and functional outcomes. The main outcome measures were Barthel index (BI) at admission and its change during 4 weeks inpatient neurorehabilitation.Results: Men had been diagnosed with osteoporosis less frequently than women but more often with type 2 diabetes mellitus, coronary artery or chronic kidney disease (p ≤ 0.01). Although twice as many women presented with pre-stroke depression compared to men, the risk of post-stroke depression detected during rehabilitation was comparable. Men were more likely to have less than 30 days between diagnosis and neurorehabilitation start than women (p < 0.03). At admission, women exhibited less autonomy, a lower BI, a higher pain score and worse 2-min walk test (2′WT) compared to men (p < 0.001). Among males osteoporosis and peripheral artery disease independently predicted BI at admission, in women it was pre-stroke depression, dementia, and arterial fibrillation. During neurorehabilitation, both sexes improved regarding BI, pain and walk tests (p < 0.001). Despite comparable rehabilitation effectiveness, women still had worse functional outcomes than males at discharge. Time after stroke to start of neurorehabilitation and length of the stay but, most strongly, the simple 2′WT at admission, and in women, pain intensity independently predicted post-stroke functional status and recovery.Conclusion: Women presented with worse functional status at admission to neurorehabilitation. Although men and women showed similar rehabilitation effectiveness, women still displayed worse clinical outcome measures and higher levels of pain at discharge. Early access and gender-sensitive, personalized post-stroke care with more focus on different comorbidities and psychosocial factors like pain levels and management, could further improve neurorehabilitation outcomes.